Contribution to the study of Parinaud syndrome - Voto Bernales, Jorge (1957)
We reviewed the history of Parinaud syndrome, since its description in 1883. There is evidence that she has experienced a definite developments due to the current understanding of the mechanisms associated with large vertical gaze area. Also discussed are the various clinical aspects of the problem, through the copious literature published after communication Parinaud. We provide 4 personal observations of Parinaud syndrome: 3 relacionodas to something more complicated neurological syndromes, and 1 similar to the classic description of Parinaud. These observations confirm the general impression of the outstanding exclusivity of this syndrome appears frequently included in more complex neurological cases. The etiology has also been different in our 4 observations; this represents the fragility of neural structures involved in vertical gaze at the various agents that damage the nervous system. The clinical course was satisfactory in 3 cases, with a significant recovery of the oculomotor disorder 2 there was 1 case fatal, and anatomical examination showed the lesions in the subthalamus-mesoencenfálica region below the posterior white commissure, including the commissural nuclei and interstitial unilaterally.